How to Teach Students What Constitutes Scientific Evidence - Don Affognon (Journal of Studies in Education, 2024)
What sets credible scientific claims apart from pervasive misperceptions and are there effective strategies for teaching college students to evaluate popular accounts of scientific evidence? The Next Generation Sciences Standards (NGSS) suggest that although the practices for developing credible scientific evidence vary across disciplines, there are common features. These include a commitment to using evidence as the basis for developing claims, gathering evidence to accept or reject student ideas about the causes of certain effects, and relying only on evidence to draw theoretical conclusions. Yet the NGSS do not clearly specify what counts as credible evidence. I defend the view that while there are no shortages of strategies for teaching evidence evaluation, the effective ones share two features: (i) they reflect how students generally interact with evidence, and (ii) they bridge the gaps between expert and nonexpert evidentiary practices.